PERANCANGAN SIGN SYSTEM SEBAGAI MEDIA INFORMASI UNIVERSITAS PARAMADINA DI KAMPUS CIPAYUNG - Siti Khodijah Lestari; Rian Dwi Antoro; Novandy Ananta Adi Putra (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2023)
The existence of a sign system in public spaces is crucial, not only as an information medium but also for playing a role in creating a conducive public environment and reinforcing the image of institutions, such as the Paramadina University campus in Cipayung. In its development, the Cipayung campus is projected to become the main campus of Paramadina University, requiring the incorporation of a sign system in the current construction of buildings. In the design process of the sign system, a concept is needed that can represent the vision and mission of the university or the values inherent in Paramadina, such as Islamic, Indonesian, and Modern values. This research aims to understand the process of designing a sign system using a descriptive-qualitative method. Data sources for this research were obtained through interviews, observations, and literature studies. Keywords: Sign System, Information Media, Paramadina University